Energy -concerving and environment -protective loosening tiller - FU JIANGANG (2017)
The utility model provides an energy -concerving and environment -protective loosening tiller belongs to agricultural machinery, include frame, handrail, the blade that loosens the soil, drive loosen the soil blade pivoted drive arrangement, battery and photovoltaic board, be equipped with the insulating layer that thermal insulation material made between photovoltaic board and electrical connections battery and the two. The photovoltaic board truns into solar energy the electric energy to and is storage battery charging, can prolong the operating time of loosening tiller, avoids the loosening tiller to appear because of the not enough unable work of electric quantity. The stepless speed regulation and control system of a construction elevator is simple in structure and convenient to use. 本实用新型提供了种节能环保松土机，属于农用机械领域，包括机架、扶手、松土刀片、驱动松土刀片转动的驱动装置、蓄电池和光伏板，光伏板与蓄电池电连接且二者之间设有隔热材料制成的隔热层。光伏板将太阳能转为电能并为蓄电池充电，可以延长松土机的工作时间，避免松土机出现因电量不足而无法工作。其结构简单、使用方便。